Molecular characterization of hemoglobin D Punjab traits and clinical-hematological profile of the patients - Pandey, Sanjay; Mishra, Rahasya Mani; Pandey, Sweta; Shah, Vineet; Saxena, Renu (São Paulo Medical Journal, 2012)
CONTEXT AND OBJECTIVE: Hemoglobin (Hb) D hemoglobinopathies are widespread diseases in northwestern India and usually present with mild hemolytic anemia and mild to moderate splenomegaly. The heterozygous form of Hb D is clinically silent, but coinheritance of Hb D with Hb S or beta-thalassemia produces clinically significant conditions like thalassemia intermedia of moderate severity. Under heterozygous conditions with coinheritance of alpha and beta-thalassemia, patients show a degree of clinical variability. Thus, our aim was to molecularly characterize the Hb D trait among individuals who were clinically symptomatic because of co-inheritance of alpha deletions or any beta-globin gene mutations. DESIGN AND SETTING: This was a cross-sectional study conducted in an autonomous tertiary-care hospital. METHODS: Complete blood count and red cell indices were measured using an automated cell analyzer. Quantitative assessment of hemoglobin Hb F, Hb A, Hb A2 and Hb D was performed by means of high performance liquid chromatography (HPLC). DNA extraction was done using the phenol-chloroform method. Molecular analyses on common alpha deletions and common beta mutations were done using the Gap polymerase chain reaction and Amplification Refractory Mutation System, respectively. RESULTS: We evaluated 30 patients and found clinical variation in the behavior of Hb D traits. In six patients, the Hb D traits were clinically symptomatic and behaved like those of thalassemia intermedia. Molecular characterization showed that three out of these six were IVS-1-5 positive. CONCLUSIONS: HPLC may not be the gold standard for diagnosing symptomatic Hb D Punjab traits. Hence, standard confirmation should include molecular studies.